Skin prick test in milk allergic patients undergoing oral immunotherapy: Does the milk form used for skin tests matter? - Bukhari, Esraa; Gabrielli, Sofianne; McCusker, Christine; Upton, Julia; Grunebaum, Eyal; Chan, Edmond S.; Beaudette, Liane; Langlois, Alexandra; Torabi, Bahar; Lejtenyi, Duncan; Clarke, Ann E.; Ke, Danbing; et al. (Frontiers in Allergy, 2022)
SPT is the most commonly used confirmatory test for an IgE-mediated milk allergy. However, food SPTs are not standardized. We aimed to assess the accuracy of SPTs with extract, diluted, and undiluted milk to detect desensitization in children with milk allergy undergoing OIT. Children with milk allergy undergoing OIT and controls were recruited from Montreal Children’s Hospital (MCH), British Columbia Children’s Hospital (BCCH) and The Hospital for Sick Children (SickKids). Participants in the active arm received a weekly increase in milk until 200 ml of pure milk was tolerated. SPT using milk extract (Omega), diluted 2% milk (1:10), and undiluted milk was done at the study entry and when 200 ml of pure milk was reached. Participants in the control arm had SPT at study entry and 12 months later before they entered the active arm. Among 53 children who reached 200 ml, the median age was 12 years and 54.7% were males. The mean decrease in wheal size at 200 ml from the baseline was 3.78mm (95%CI 2.55-5.01), 5.05 mm (95% CI 3.68-6.41), and 5.05mm (95% CI 3.29-6.80) for milk extract, diluted and undiluted milk respectively. Among 32 controls, the median age was 10 years and 62.5% were males. There was no significant change in wheal diameter over a one-year period regardless of the skin test method. Response to extract behaved similarly to whole food (Diluted and undiluted) and thus can be used to follow sensitization in the context of a desensitization program.